2009
DOI: 10.1080/15564900902771325
|View full text |Cite
|
Sign up to set email alerts
|

“I Am a Muslim and My Dad is an Alcoholic—What Should I Do?” Internet-Based Advice for Muslims About Alcohol

Abstract: This article analyzes 113 fatwas (pieces of advice from Muslim scholars) in response to Internet usercontributed questions about correct behavior in situations involving alcohol. The fatwas are from IslamOnline.net, a popular Islamic Web site. Most of the questions on the English site are submitted by individuals living in non-Muslim countries, who are more likely to confront difficult situations relating to alcohol. In spite of the general condemnation of alcohol consumption in Islam, many individuals face et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…But Muslim religiosity may also account as a causal factor of less smoking through a psychological pattern of health promoting lifestyle which Islamic teaching is embedded in. One of the arguments of Islamic prohibitions of alcohol consumption are with reference to its negative effects on health ( Michalak et al, 2009 ). Both pathways comply with the biopsychosocial model.…”
Section: Discussionmentioning
confidence: 99%
“…But Muslim religiosity may also account as a causal factor of less smoking through a psychological pattern of health promoting lifestyle which Islamic teaching is embedded in. One of the arguments of Islamic prohibitions of alcohol consumption are with reference to its negative effects on health ( Michalak et al, 2009 ). Both pathways comply with the biopsychosocial model.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that AUD was more prevalent among the Christians is in support of previous studies in Nigeria [ 26 , 28 ]. This may be adduced to the general condemnation of alcohol consumption in Islam [ 29 ]. The association of ethnicity with AUD as reported in the current study in which the Yoruba ethnic groups, compared with other ethnic groups were less likely to have AUD was also noted in a previous study among the military population [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism is that those who develop harmful drinking patterns are selected out among those regular religious participants through the negative reinforcement of at risk drinking behavior [ 36 ]. Several studies have shown religious affiliation is strongly associated with alcohol consumption in several African states [ 13 , 18 ], and further longitudinal investigations are required to elucidate causal pathways. South African low-risk drinking men had the highest frequency of regularly engaging in activities with friends, and this is similar to results among older adults in the US showing social participation is associated with more alcohol consumption, and indicating drinking is undertaken for social reasons [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other health behaviors, such as smoking, and socio-cultural factors, such as marital status and ethnicity, have been found to be associated with risky drinking behaviors among older adults in South Africa, with considerable differences between the sexes [ 17 ]. Religious affiliation is a strong predictor of drinking behavior in South Africa among both genders, where studies consistently observe that Christians imbibe and Muslims abstain [ 13 , 18 ].…”
Section: Introductionmentioning
confidence: 99%